92.2k views
1 vote
What is 4 (m + n) -5 (m - n) ?

1 Answer

7 votes

Answer:

Explanation:

for this situation we do distributive property{in distributive property [in this situation ] we will (multiply 4 by m & n) - (multiply 5 by m & n)=

4m + 4n - 5m - 5n =

(4m -5m) - (4n - 5n) =

-1m - (- 1n) =

-1m + 1n

and always remember to go in alphabetical order = m comes before n, x comes before y or z.

User Adam Straughan
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.